The Jigsaw Cooperative Learning Model in Islamic Religious Education to Develop Students' Emotional Intelligence - Purnama Sari, Nurul; Basyar, Syaripudin; Jatmiko, Agus (Bulletin of Science Education, 2024)
This study investigates the correlation between emotional intelligence in Islamic teachings and the embodiment of morality as human behaviour. Carried out at SMA YP UNILA Bandar Lampung, the research spanned from October 2023 to January 2024, utilizing a descriptive qualitative methodology. Islamic education teachers were the subjects. Data collection involved observation, interviews, and documentation, with analysis employing reduction, presentation, and concluding. Validity was ensured through triangulation techniques and sources. Supportive factors encompassed collaborative efforts among school personnel, adequate facilities, extracurricular activities, and teacher competency. Conversely, hindering factors comprised students' disinterest in religious activities, insufficient parental support, restricted learning time, non-compliance with school rules, and academic pressure. The study's findings align with Daniel Goleman's emotional intelligence theory, positioning emotional intelligence as the bedrock for various other intellectual capacities. Keywords: Cooperative Learning, Islamic Religious Education, Emotional Intelligence